Foreign Ownership and Transfer Pricing on Tax Avoidance with Leverage as a Moderation - Juendiny Chrisna Ekasari; Ayuvera Rifani Ray; Suhartati Suhartati (eCo-Fin, 2025)
This study aims to explore the factors that influence corporate tax avoidance by examining the roles of foreign ownership and transfer pricing, along with leverage as a moderating variable. The research provides empirical insights into how these variables interact and contribute to tax avoidance practices. The study’s findings are relevant for various stakeholders, including government regulators, investors, corporate management, tax consultants, and academics. The data used are secondary data obtained from the official website of the Indonesia Stock Exchange (IDX), covering mining companies listed between 2015 and 2019. A total of 20 companies were selected, resulting in 100 firm-year observations. The analytical method employed is Moderated Regression Analysis (MRA). The results reveal that both foreign ownership and transfer pricing have a positive effect on tax avoidance. Furthermore, leverage is found to strengthen the relationship between foreign ownership and tax avoidance. However, leverage does not moderate the relationship between transfer pricing and tax avoidance.